Determination of safe distance between roadway and school buildings to get acceptable school outdoor noise level by using noise barriers - Avsar, Y; Gonullu, MT (PERGAMON-ELSEVIER SCIENCE LTD, 2005)
Noise nuisance caused by road or highway depends on three main reasons; (1) type, speed and number of vehicles, (2) road surface structure sort and (3) characteristics of buildings and number of inhabitants. School buildings are often subjected to higher outdoor noise levels. Hence intelligibility of lessons by students is decreased. This study deals with relations between vehicle speeds and noise levels. Following the road study, without using any noise propagation processes, convenient school building-roadway distances were searched according to possible roadway traffic loads, number of lines and vehicle speeds. In this course, school building-road distance, barrier types and their arrangements, road surface types and vehicle speed limitations were offered. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: Construction & Building Technology; Engineering